Pengaruh Stres Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Perkebunan Minanga Ogan Baturaja - Noviansyah Noviansyah; Zunaidah Zunaidah (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2011)
The title of the is “The influence of Job Stress and Work Motivation toward Employee Performance at PT. Perkebunan Minanga Ogan Baturaja”. The purpose of the study was to fond out the influence of job stress and work motivation as an independent variable. The contribution which was expected could give valuable benefit with practically and theoretically. It was expected could give an idea about the influence of job stress and work motivation toward employee performance theoretically with, it was expected could add other reference and contribution for other researchers, and give experience for society industry  issues.The descriptive method and regression analysis, were used in this study and the data was collected by using questionnaire technique which arranged based on theoretically study. the statement in the questionnaire has been tested its validity and reliability. All the employee at PT. Perkebunan Minanga Ogan Baturaja with the total 78 employee as a respondent.The result of research showed the first hyphotesis that was job stress had significant influence toward employee performance simultaneously. And based on the result of regression analysis, the influence of job stress variable and work motivation toward employee performance at PT. Perkebunan Minanga Ogan Baturaja could be proved. That lowest or highest job stress had influenced for level of employee performance low (it optimum), it could be concluded that over job stress and low motivation made frustation/underpressure and decrease of performance And finally, job stress more influenced : than work motivation toward employee performance. Keywords: Job Stress, Work Motivation and Employee Performance